Pengetahuan Akseptor Tentang KB Suntik 3 Bulan Dengan Ketepatan Waktu Kunjungan Ulang di BPRB Bina Sehat Kasihan, Bantul, Yogyakarta - Sri Lestari; Susiana Sariyati; Wahyuningsih Wahyuningsih (Alma Ata University Press, 2015)
Family planning (FP) program has important role in realizing Indonesian people prosperous, besides health and education program. Contraceptive injection high effectiveness if the injection carried out regularly and appropriate schedule. Promptness revisit in FP injection is inﬂ uenced by acceptors knowledge about FP injection and supported with a good memory. The knowledge level is one factor that causing acceptors choosing or not a method of contraception. The purpose of this study was to know relationship between knowledge level of acceptors and three months contraception injection with promptness revisit. This study was an observational analytic with cross sectional design. Technique sampling used was purposive sampling, resulted on 63 respondents. The study was done by granting the questionnaire to acceptors who revisit at BPRB Bina Sehat Kasihan Bantul In July 2014. Test analysis used chi-square. The results showed that knowledge of acceptors family planning about 3 months injection was 57 (90.5%) respondents in high knowledge. Timeliness revisit of acceptors 3 months injection was 60 (95.2%) respondents revisit timely. According to the analysis of using formulas chi-square test with standard signiﬁ cance 0.05 and degrees of freedom 1, obtained chi-square count was 0.332 or p-value 0.565 while chi-square table was 3.841. In conclusion, there was no relationship between knowledge level of acceptors family planning and 3 months injection with promptness revisit at BPRB Bina Sehat Kasihan Bantul.